Frugal innovation: a proposal of an instrument to measurement - Rossetto, Dennys Eduardo (2018)
In both academia and the press, Frugal Innovation has been gaining more space and attention from researchers and managers, mainly for showing itself as an alternative for competitiveness in times of crisis and increasingly scarce resources. Despite the growing number of published articles on Frugal Innovation, there is still a lack of instruments that allow the measurement and quantification of this phenomenon to allow more precise and quantifiable studies to be carried out. Furthermore, due to the wide concepts of Frugal Innovation still into consolidation process, would be very useful for managers and entrepreneurs an instrument that allows the identity and to guide the companies who desire directions on way to the development of frugal offers, besides constitute a meaningful theoretical contribution. On this thesis we purpose a scale for identify and measure the Frugal Innovation, presenting the results of five data collection in three different countries (Brazil, USA, and India), with all the development process, the items’ refinement through an Exploratory (EFA), Confirmatory Factor Analysis (CFA) and final validation of the scale based on 1130 firm’s data. A broad review of the literature is presented with a rescue of main papers published, as well as an analysis of the dimensionality of the construct, all definitions found in the literature. Also, an improvement in the definition of frugal innovation is proposed through by creating a frugal ecosystem. All procedures follow the steps based on Churchill’s paradigm (Churchill, 1979) that was updated by Mackenzie, Podsakoff, and Podsakoff (2011). On the first stage were generated 66 items based on a wide literature review. The content validation was realized through personal interviews with 12 specialists (academics and managers), as result 20 items were retained. In the sequence, the face validation was realized with 22 managers aiming for the improvement of the clarity and the understanding of the items, resulting in 12 retained items. With the 12 items remains, a survey was realized composed by 191 Brazilian firms where was realized a Factorial Exploratory Analysis (EFA) as a first purification process, in which the adjustment of all statistical indices was obtained. As result were obtained three dimensions (1) Focus on Core Functionality and Performance; (2) Substantial Cost Reduction; and (3) Creation of a Frugal Ecosystem, all composed by 9 items, three items on each dimension. A second survey round was realized with 247 Brazilian firms, and with these data was realized a Confirmatory Factor Analysis (CFA) and internal consistency verification, where all adjustments were obtained again. The questionnaire was submitted to back-translation procedures to reach the translation validity and then, were realized another two surveys, with 250 American firms and with 300 Indian firms for final validation purposes. As result, others validation was obtained like the convergent validity, discriminant validity, reliability checking and the nomological validity (through the application of another scales). The scale was applied to Indian firms aiming to get results from another emerging country. To contribute to the discussion about the Frugal Innovation is or not appropriated only for emerging countries or if also a phenomenon that can occur in developed countries, this scale is also was applied to US firms. With this validated scale, this study contributes to the carry out of other researchers, allowing the get results from other countries, developed or in developing process, for comparative researchers and for a better understanding of the relations of the Frugal innovation with other phenomena.